Health semiosphere in parks: case study in Quito and Madrid - Santillán Trujillo, Mónica; Rodríguez Arriero, Miguel Ángel; Villavicencio Álvarez, Víctor; Abril Porras, Víctor; Cordero Espinoza, Tomás (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: The parks importance as green environments for healthy recreation is not assumed in their real dimension given their health benefits, although the World Health Organization recommends the availability of a minimum of 9 m2 of green space per person. Various international organizations recognize that the park’s main essential services for communities are economic value, health and environmental benefits. Objective: To determine the health semiosphere in emblematic parks of Quito and Madrid. Methods: A mixed investigation was carried out using semiotics as the main tool. For the information gathering, the citizen survey technique of Quito and Madrid was applied, as a basis for a comparative analysis that allowed measuring the perception modes. Results: Intrinsic health activities were determined as part of the park’s semiosphere, both in Quito and Madrid. In the first city, recreation was recognized as the main one, and sports in the second city; as well as cultural and recreational activities such as the relevant ones to be enhanced. Conclusions: The park’s main activities are intrinsically linked to citizen’s health, so their semiosphere is based on their determination with the aim of repowering them.